[Ln6O8] Cluster‐Encapsulating Polyplumbites as New Polyoxometalate Members and Record Inorganic Anion‐Exchange Materials for ReO4− Sequestration. Issue 17 (17th June 2019) - Lin, Jian; Zhu, Lin; Yue, Zenghui; Yang, Chuang; Liu, Wei; Albrecht‐Schmitt, Thomas E.; Wang, Jian‐Qiang; Wang, Shuao
Abstract: Various types of polyoxometalates (POMs) have been synthesized since the 19th century, but their assortment has been mostly limited to Groups 5 and 6 metals. Herein, a new family of POMs composed of a carbon group element as the addenda atoms with two distinct phases, LnPbOClO4 ‐1 (Ln = Sm to Ho, Y) andLnPbOClO4 ‐2 (Ln = Er and Tm) is reported. Both structures are built from [Ln6 O8 ] rare‐earth metal hexamers being incorporated in [Pb18 O32 ]/[Pb12 O24 ] polyplumbites, and unbound perchlorates as charge‐balancing anions. Impressively, YPbOClO4 ‐1 andErPbOClO4 ‐2 exhibit exceptional uptake capacities (434.7 and 427.7 mg g −1 ) toward ReO4 −, a chemical surrogate for the key radioactive fission product in the nuclear fuel cycle 99 TcO4 −, which are the highest values among all inorganic anion‐exchange materials reported until now. The sorption mechanism is clearly elucidated and visualized by single‐crystal‐to‐single‐crystal structural transformation fromErPbOClO4 ‐2 to a perrhenate‐containing complexErPbOReO4, revealing a unique ReO4 − uptake selectivity driven by specific interaction within Pb···O‐ReO3 − bonds. Abstract : A family of [Ln6 O8 ]‐encapsulating polyplumbite clusters with the highest adsorption capabilities toward ReO4 − among all inorganic materials is developed, representing a brand new family of polyoxometalates based on Group 14 element with application potentials in the nuclear fuel cycle, which overcomes the critical drawbacks of low sorption capacity and poor selectivity for traditional inorganic anion‐exchange materials toward ReO4 − /TcO4 − sequestration.